NGI IP service management system architecture and application supporting workflow management and policy management - ZHANG Ruo-ying1; MENG Luo-ming2; QIU Xue-song2 (Tongxin xuebao)
In order to realize the service process automation, and scalable and dynamic service management of NGI service, and adapt to the new service and efficient service management, on the basis of WfMC workflow reference model and IETF policy framework, the architecture of NGI IP service management system supporting workflow management and policy management was proposed. The components and their functions were analyzed in detail. And based on this architecture an application scenario instance of the fulfillment process flow of NGI IP service was given.